Analisis Penurunan Konsentrasi Gas Karbon Monoksida (CO) Pada Saluran Ventilasi di Area Belokan Menggunakan Model Fisik Terowongan Skala Laboratorium - Ririn Yulianti; Panjaitan Novi Hartami; Edy Jamal Tuheteru; Yuga Maulana; Irfan Marwanza; Sekar Tika Sari (Jurnal Geomine, 2023)
Carbon monoxide (CO) gas is one of the harmful and toxic gases derived from the residue of blasting and incomplete combustion of mining equipment machines in underground mines. CO gas dilution is carried out with the intention of unsafe conditions in the mining area. The purpose of this study was to determine the decrease in CO gas based on the value of the diffusion coefficient and by making a 1:10 scale tunnel model with a 90° turning vent duct flow direction using an elbow according to the actual situation. XC 13 B and XC 13 NRTH in the Cikoneng block, PT Cibaliung Sumberdaya is used as a reference for the tunnel model. The study was carried out with variations in the position of the vent duct to determine the speed of decrease in the CO concentration tested. This study was conducted using secondary and primary data which is expected to get the results of the influence of the concentration of CO gas itself and the influence of vent duct placement on the direction of flow on the decrease in CO gas concentration.